Training in Waqf Administration for Micro, Small, and Medium Enterprises: A Novel Paradigm of Community-Centric Sharia Economic Framework in the Mujahadah Mosque Vicinity of Rintis Village, Pekanbaru - Wali Saputra (Jurnal Ragam Pengabdian, 2025)
The present community service initiative seeks to enhance individuals' capabilities in the effective administration of waqf through the empowerment of Micro, Small, and Medium Enterprises (MSMEs) within the framework of the sharia economy. This training was meticulously crafted in response to the inadequate utilization of waqf assets in bolstering the local economy, as well as the constrained access to capital for MSMEs at the grassroots level. The methodologies employed for implementation encompass preparatory stages, participatory training, evaluative measures, and advanced mentorship. The event transpired over a duration of three days, engaging 45 participants hailing from diverse backgrounds, including MSME practitioners, nadzir, religious leaders, and village youth. The materials disseminated comprised productive waqf literacy, management of sharia-compliant MSMEs, and simulations for waqf-based business planning. The outcomes of the activities indicated a notable enhancement in the participants' comprehension, the establishment of three waqf-oriented business groups, and tangible support from local authorities manifested through the provision of assets and formal institutional recognition. This initiative substantiates the proposition that waqf can be optimized as a mechanism for community economic empowerment, provided it is managed in a collaborative and community-oriented manner. The waqf management model for MSMEs developed through this training demonstrates the potential for replication across various regions, thereby contributing to the sustainable and inclusive economic fortification of the ummah. Furthermore, the program promotes the cultivation of a sharia economic ecosystem that positions communities as primary stakeholders rather than mere beneficiaries.